Cooling and Comfort: The COMFORTNeo-scale during therapeutic hypothermia after perinatal asphyxia. Issue 6 (December 2018) - ,; ,; van Kaam, A.H.; van Straaten, H.L.; Zonnenberg, I.; Dijk, P.H.; Dudink, J.; Rijken, M.; van Heijst, A.; Dijkman, K.P.; Cools, F.; Zecic, A.; et al.
Abstract: The therapeutic effect of moderate hypothermia in infants with HIE after perinatal asphyxia can be counteracted by stress which should therefore be minimized. Objective: of study was to gain insight in the COMFORTNeo-scale to measure stress during therapeutic hypothermia. Stress was measured prospectively by means of the COMFORTNeo-scale (CNS), twice a day, during hypothermia-, rewarming- and stabilization phase in a cohort of 133 neonates with perinatal asphyxia who participated in the PharmaCool study. A total of 994 CNS scores were collected; median score CNS 9 (IQR 7–11). Despite analgesic, sedative and anticonvulsant drugs 10% of the scores indicated moderate to severe stress during treatment. The use of these drugs as well as mechanical ventilation interfered with CNS score (respectively odds ratio 0.74 and 0.61) Interference of aEEG, hypothermia phase and gender were not confirmed. The COMFORTNeo-scale can, with the necessary caution, be used for the assessment of stress during therapeutic hypothermia treatment. Other options should be explored.